Scaphoid nonunion: what is the role of the Zaidemberg 1, 2 intercompartmental supraretinacular arterial flap?. (January 2018) - Henry, Mark
The reported results for the treatment of scaphoid nonunions with non-vascularized grafts are based on observational studies with a high variability in union rates from 38%–100% and time to union from 6–18 weeks, and there is also a lack of a standard classification. Meta-analyses and systematic reviews have been presented to better support conclusions from large pools of data (604 to 5246 cases), but their interpretation remains limited because of lack of uniformity in the studies analysed. Several authors have presented results from the Zaidemburg flap, with highly variable outcomes despite using the same technique; union rates have ranged from 27%–100% achieved between 6.5–19 weeks. Technical details that may be responsible for the discrepancies are discussed. There is a need for a validated prognostic classification system for scaphoid nonunions that can allow comparisons between outcome studies.